Diversity and genetic structure of Quercus crassifolia in managed forest and local use sites in Sierra Juárez, Oaxaca - Gorgonio Ramírez, Montserrat; Clark Tapia, Ricardo; Campos Contreras, Jorge; Montalvo Reyes, Alejandro; Alfonso Corrado, Cecilia Liana (Instituto de Ecología, A.C., 2017)
Oaks play an important ecological, social and economic role; however, few studies evaluate the effect of human activities on population genetics of species in genus Quercus. The objective of this work was to evaluate the effect of forest management and local use on genetic diversity of Quercus crassifolia. Eight nuclear microsatellites were used for 12 populations, covering six forest sites that had been managed and six sites of local use. The results indicate that the species has an average moderate genetic diversity (He = 0.764 ± 0.014), without signifitive differences between, sites with local use and forest management. We found a low genetic structure among population (FST = 0.025 ± 0.047 y RST = 0.157 ± 0.135), due to a moderate gene flow (Nem = 6.7), which is responsible for the absence of loci under directional selection. The excessive extraction of individuals affects the population viability and regeneration of the species, which in the future may have a negative effect on the genetic diversity and the processes of genetic differentiation among populations. This study provides essential information that will be useful for decision-making in conservation activities and management plans for Q. crassifolia in Sierra Juárez, Oaxaca.